Design Computing and Cognition '16 - Gero, John. S.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book gathers the peer-reviewed and revised versions of papers from the Seventh International Conference on Design Computing and Cognition (DCC'16), held at Northwestern University, Evanston (Chicago), USA, from 27-29 June 2016. The material presented here reflects cutting-edge design research with a focus on artificial intelligence, cognitive science and computational theories. The papers are grouped under the following nine headings, describing advances in theory and applications alike and demonstrating the depth and breadth of design computing and design cognition: Design Creativity; Design Cognition - Design Approaches; Design Support; Design Grammars; Design Cognition - Design Behaviors; Design Processes; Design Synthesis; Design Activity and Design Knowledge. The book will be of particular interest to researchers, developers and users of advanced computation in design across all disciplines, and to all readers who need to gain a better understanding of designing.
DESIGN CREATIVITY -- Reducing Information to Stimulate Design Imagination -- Novelty, Conventionality, and Value of Invention -- Characterizing Tangible Interaction During a Creative Combination Task Structure -- Dissecting Creativity: How Dissection Virtuality, Analogical Distance, and Product Complexity Impact Creativity and Self-efficacy -- DESIGN COGNITION - DESIGN APPROACHES -- What Can We Learn From Autistic People About Cognitive Abilities Essential To Design? An Exploratory Study -- Solution-oriented Versus Novelty-oriented Leadership Instructions: Cognitive Effect on Creative Ideation -- A Protocol Study of Cognitive Chunking in Free-Hand Sketching during Creative Ideation in Design -- A Systematic Review of Protocol Studies on Conceptual Design Cognition.-DESIGN SUPPORT -- Is Biologically Inspired Design Domain Independent? -- A Meta Analytic Approach for Uncovering Neural Activation Patterns of Sustainable Product Preference Decisions -- Second Guessing - Designer Classification of Problem Definition Fragments -- The Analysis and Presentation of Patents to Support Engineering Design -- DESIGN GRAMMARS -- Classifications of Shape Grammars -- From Shape Computations to Shape Decompositions -- Automated Induction of General Grammars for Design -- Generative Shape Design using 3D Spatial Grammars and Simulation -- DESIGN COGNITION - DESIGN BEHAVIORS -- Comparing Two Communication Models of Team Design Activities -- Individual Differences in Tendency for Design Fixation -- Functional Thinking: A Protocol Study to Map Modeling Behavior of Designers -- To Copy or not to Copy: The Influence of Instructions in Design Inspiration and Fixation Experiments -- DESIGN PROCESSES -- A Self-Organizing Map Based Approach to Adaptive System Formation Grammars -- Utilizing Markov Chains to Understand Operation Sequencing in Design Tasks -- Designerly Pick and Place: Coding Physical Model Making as Preparation for Better Robotic Interaction -- Knowledge Distribution and the Effect of Design Tools on theDesign Process -- DESIGN SYNTHESIS -- A Heuristic Approach for the Automated Generation of Furniture Layout Schemes in Residential Spaces -- 3DDJ: An Analytical and Generative Design System for Synthesizing High Performance Textures from 3D Scans -- Automated Best Connected Rectangular Floor Plans -- Individual Coffee Maker Design Using GraphBased Design Languages -- DESIGN ACTIVITY -- Translating Analytical Descriptions of Cities into Synthetic Urban Design Models -- Exploring the Cognitive Dynamics of Product Adoption -- Characterising the Visual Information Interaction of Engineers -- Personalised Specific Curiosity for Computational Design Systems -- DESIGN KNOWLEDGE -- Experiences with Large Learner Data for Understanding How People Design: Insights and Lessons Learned -- Generalizability of Document Features for Learning Rationale -- The Topology of Social Influence and the Dynamics of Design Product Adoption -- Using Graph Complexity Connectivity Method to Predict Information from Design Representations: A Comparative Study -- Identifying Latent, Time Dependent Product Features From Online Reviews -- Author index.
Keywords: Engineering design; Artificial intelligence; Cognitive psychology; Engineering Design; Artificial Intelligence; Cognitive Psychology